Rules versus discretion in fiscal policy - Carluccio Bianchi; Mario Menegatti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
This paper purports to apply the Kydland-Prescott framework of dynamic inconsistency to the case of fiscal policy, by considering the trade-off between output and debt stabilization. The Government budget constraint provides the link between debt dynamics and the level of activity, influenced by fiscal policy. Contrary to what happens in the monetary policy framework, however, a commitment is not always superior to discretion, even in the absence of uncertainty, but only when the public debt-GDP ratio is sufficiently large. The introduction of uncertainty, as usual, implies a reduction in the net benefit generated by the adoption of a fixed rule.
Keywords: E61; E62; H62; H63; H68; 330; rules; discretion; time inconsistency; fiscal policy